Effects of topical treatment of sodium butyrate and 5-aminosalicylic acid on expression of trefoil factor 3, interleukin 1β, and nuclear factor κB in trinitrobenzene sulphonic acid induced colitis in rats. Issue 964 (3rd February 2006) - Song, M; Xia, B; Li, J
Abstract : Background and Aims: Butyrate enemas have been shown to be effective in treatment of ulcerative colitis, but the mechanism of the effects of butyrate is not totally known. This study evaluates effects of topical treatment of sodium butyrate (NaB) and 5-aminosalicylic acid (5-ASA) on the expression of trefoil factor 3 (TFF3), interleukin 1β (IL1β), and nuclear factor κB (NFκB) in trinitrobenzene sulphonic acid (TNBS) induced colitis in rats. Methods: Distal colitis was induced in male Wistar rats by colonic administration of TNBS and colonically treated with NaB, 5-ASA, combination of NaB and 5-ASA, and normal saline for 14 consecutive days. Colonic damage score, tissue myeloperoxidase (MPO) activity, TFF3 mRNA expression, serum IL1β production, and tissue NFκB expression were determined, respectively. Results: Treatment of NaB, 5-ASA, and the combination improved diarrhoea, colonic damage score, and MPO activities, increased TFF3 mRNA expression, and decreased serum IL1β production and tissue NFκB expression. The combination therapy of NaB and 5-ASA had better effects than any other single treatment. Conclusions: The combination of topical treatment of NaB and 5-ASA was effective for relieving and repairing colonic inflammation and the effects were related to stimulation of TFF3 mRNA expression and down-regulation of IL1β production and NFκB expression.